Od administrowania do zarządzania publicznego - transformacja stanowiąca warunek efektywnego zarządzania gminą oraz przedsiębiorstwami sektora publicznego - Flieger, Michał (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The aim of this article is to show the process of changes which take place in public sector management and local government management. The author explains the changes by pointing out the differences between administration, management and leadership. The similarities of public and business sector were shown, revealing the possibilities to implement the rules of business management in the public sector. These similarities result from the need to act towards development, competition, effective planning and creating the product which provides the organization with its success. Further, public management was defined and basic differences between public management and administration were shown. Public management is the detailed discipline of management science, whose main area of inteiest is management in public sector organizations. Administration, defined as meeting law requirements is just a part of public management. The basic elements of public management, which is planning, organizing, leading and control were also explained. The third part of this article defines the idea of public manager. It is a person who is one of the conditions of the transformation from administration to public management. The main objectives of this position were also stated. Public manager is a person whose aim is to implement management process in his daily routine. It must be a person who meets a lot of requirements, both educational and personal. Effective manager should have management knowledge, be an entrepreneur, creative, persistent, charismatic, and honest. This approach underlines the differences between part of public leaders who are passive and have limited professional knowledge in management subject. The ending part of this article summarizes the idea of public management and public manager. The author gives practical advice as for the necessary changes in the process of leaders selection. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 151-158